Website quality: its impact on the users / Norhidayah Ali ... [et al.] - Ali, Norhidayah; Andin Salamat, Azni Syafena; Zainal Abidin, Nor Zaini (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
The pandemic has swayed individuals to shift from traditional platforms towards online platforms in performing their daily routines such as working, teaching, learning, information searching, purchasing and others. When going online, most users are certainly looking for better website quality. This is due to websites being a company's front door to their business. Thus, the quality of the company's entrance is essential because it can either attract or retract users as well as buyers. Furthermore, it is remarked that website quality is a vital indicator in impacting users' behaviors; be it their intention, satisfaction or loyalty. Website quality contains indicators such as website design quality, system quality, and information quality. Website design comprises site navigation, appearance, and competency (Shchiglik & Barnes, 2004). System quality is the overall performance of the website. In comparison, information quality includes "accurate, timely and reliable information" (Shchiglik & Barnes, 2004). Online business is a commercial transaction that comprises sharing information across the internet. It emphasizes on information and communication technology to allow the social and business activities among individuals, groups, and other businesses, using a collection of web pages known as the company's website. Online businesses should constantly improve their website quality, especially in gaining positive behavior towards their products and services, and in turn, generate a better brand image and returns. One of the online companies with a high-quality website is Amazon.com, Inc. (Brush, 2018). Design-wise, it leverages on eye-catching colors and visuals to create an engaging and seamless user experience. The simplicity of its interaction, and one-click purchase and shopping by voice on Alexa define the high quality of its website system. Quality information is provided by its products' detail pages and built-in search interface, with filters, category navigations and recommendations, which seamlessly adapt to users' contextual choices.